Transforming Entrepreneurship Education: Connecting Green Education, Personality, and Green Entrepreneurial Orientation - Aziyah, Rantiyas Kholifatul; Melati, Inaya Sari (Journal of Educational Sciences, 2025)
Global warming has become an environmental issue that requires serious attention. Schools play a strategic role in fostering environmental awareness through green education, which aims to develop students' adaptive and environmentally conscious character. This study analyzes the influence of green education, personality traits, and green entrepreneurship practices on students' green entrepreneurial orientation. A quantitative approach was employed in this study, using purposive sampling, involving 157 ninth-grade students from SMP Negeri 22 Semarang. Data were processed using multiple linear regression analysis and path analysis with SPSS version 30. The results indicate that green education and green entrepreneurship practices significantly influence green entrepreneurial orientation, whereas personality traits do not have a direct effect. The findings highlight the importance of environmental education in shaping students' awareness and green entrepreneurial orientation as an initial step in addressing environmental issues within schools.